2018
DOI: 10.1007/s12010-018-2824-1
|View full text |Cite
|
Sign up to set email alerts
|

Autotrophic, Heterotrophic, and Mixotrophic Nitrogen Assimilation for Single-Cell Protein Production by Two Hydrogen-Oxidizing Bacterial Strains

Abstract: To recover a nitrogen resource from high-ammonia-nitrogen wastewater, two amphitrophic hydrogen-oxidizing bacteria (HOB), Paracoccus denitrificans Y5 and P. versutus D6, capable of nitrogen assimilation for single-cell protein (SCP) production were isolated. These two HOB strains could grow autotrophically with H as an electron donor, O as an electron acceptor, CO as a carbon source, and ammonia nitrogen (NH-N) as a nitrogen source. The cell molecular formulas of strains Y5 and D6 determined by autotrophic cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…could trigger methane biocatalysis with extracellular metabolites formed, such as formate, acetate, succinate, lactate, 3hydroxybutyrate and even H 2 (Kalyuzhnaya et al, 2013), that can be easily consumed by the HOB. The heterotrophic volumetric productivity of HOB is higher than that of autotrophic production (Dou et al, 2019), which can be attributed to gas-liquid mass transfer limitations. Therefore, the addition of HOB to MOB cultures has a benefit that, apart from eliminating the soluble metabolites of methanotrophic bacteria (which can further cause inhibition), it increases biomass concentration and productivity.…”
Section: Co-cultivation Of Mob and Hob For Microbial Protein Production Could Enable System Stability And Higher Resource Utilization Effmentioning
confidence: 95%
See 2 more Smart Citations
“…could trigger methane biocatalysis with extracellular metabolites formed, such as formate, acetate, succinate, lactate, 3hydroxybutyrate and even H 2 (Kalyuzhnaya et al, 2013), that can be easily consumed by the HOB. The heterotrophic volumetric productivity of HOB is higher than that of autotrophic production (Dou et al, 2019), which can be attributed to gas-liquid mass transfer limitations. Therefore, the addition of HOB to MOB cultures has a benefit that, apart from eliminating the soluble metabolites of methanotrophic bacteria (which can further cause inhibition), it increases biomass concentration and productivity.…”
Section: Co-cultivation Of Mob and Hob For Microbial Protein Production Could Enable System Stability And Higher Resource Utilization Effmentioning
confidence: 95%
“…The general advantages of using HOB for MP production were summarized from Dou et al (2019): 1) compared to other MP types, HOB have higher protein content (i.e., 40-60% for microalgae, 30-45% for fungi and 45-55% for yeasts) (Nasseri et al, 2011); 2) they are metabolically versatile, and can switch from autotrophic to heterotrophic mode; 3) even though they are autotrophic, they do not get limited by light availability; 4) they contain intracellular products with prebiotic functions (i.e., polyhydroxybutyrate (PHB)); and 5) they fix CO 2 to protein. Similar advantages can be reported for MOB.…”
Section: Co-cultivation Of Mob and Hob For Microbial Protein Production Could Enable System Stability And Higher Resource Utilization Effmentioning
confidence: 99%
See 1 more Smart Citation
“…Once a lab is established to feed mixtures of H 2 and O 2 to bacteria, HOB are fairly easy to isolate. They have been detected in many different environments, such as Antarctic subglacial lakes, temperate soils, and hot hydrothermal vents [13][14][15][16][17][18].…”
Section: Micro-organismsmentioning
confidence: 99%
“…Before, the team used hydrogen oxidation bacteria to produce SCP ( Dou et al., 2019 ). The results showed that Paracoccus denitrificans Y5 could grow autotrophically with H 2 as an electron donor, CO 2 as a carbon source, and ammonia-nitrogen (NH 4 + -N) as a nitrogen source to produce SCP.…”
Section: Introductionmentioning
confidence: 99%